A MODEL OF SPEAKING LESSON PLAN BASED CONTEXTUAL FOR PRIMARY SCHOOL TEACHER EDUCATION STUDENTS - Dayu Retno puspita; Nuruddin Nuruddin; Zainal Rafli (JALL (Journal of Applied Linguistics and Literacy), 2022)
Lesson plans are an essential component of teaching. English lecturers must be skilled, creative, and innovative in order to enable students to absorb language learning knowledge easily and effectively. In teaching English speaking skills in class, lecturers need good preparation by designing lesson plans as directions or roadmaps for all activities carried out by lecturers and students in class to achieve appropriate and effective competencies so as to create fun and interesting teaching. Students in primary school teacher education are given with English subject as a provision that will be offered in primary schools to aid their performance as prospective primary school teachers in teaching English. Speaking abilities are one of the skills that students pursuing a degree in primary school teacher education must have in order to master the capacity to communicate in spoken English. The purpose of this paper is to provide information about contextual-based English speaking lesson planning. The process of developing model speaking lesson plan based contextual used an educational research and development (R&D). a number of instruments were used, i.e. interview, classroom observation, and document. This study can be useful for English lecturers and researchers as a guide to teaching speaking English using a contextual approach. This review paper delves into the body of research on the term problem of English speaking skills in primary school teacher education, lesson plans, aspects of lesson plans, activity in teaching speaking, teaching cycle, and a sample of lesson plans’ procedure using teaching speaking based on a contextual approach. The more lecturers plan, the better they will be.